2020
DOI: 10.1101/2020.08.29.271015
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Silicon Nitride Inactivates SARS-CoV-2in vitro

Abstract: IntroductionSevere acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which is responsible for the COVID-19 pandemic, remains viable and therefore potentially infectious on several materials. One strategy to discourage the fomite-mediated spread of COVID-19 is the development of materials whose surface chemistry can spontaneously inactivate SARS-CoV-2. Silicon nitride (Si3N4), a material used in spine fusion surgery, is one such candidate because it has been shown to inactivate several bacterial species an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…Recent studies have shown that AP2 silicon nitride powder kills SARS-CoV-2 faster than other antipathogenic materials [188]. As a biomaterial, it also offers more advantages than titanium or PEEK [189]. This material is currently approved by the FDA for the manufacture of medical devices such as [190]: cervical and thoracic spine devices, joint replacement, and its use for dental implants is even being considered [191].…”
Section: Fda Authorizationmentioning
confidence: 99%
“…Recent studies have shown that AP2 silicon nitride powder kills SARS-CoV-2 faster than other antipathogenic materials [188]. As a biomaterial, it also offers more advantages than titanium or PEEK [189]. This material is currently approved by the FDA for the manufacture of medical devices such as [190]: cervical and thoracic spine devices, joint replacement, and its use for dental implants is even being considered [191].…”
Section: Fda Authorizationmentioning
confidence: 99%
“…Silicon nitride has been shown to inactivate several bacterial species and viral strains including SARS-CoV-2, while mammalian cells would remain unaffected [83]. SARS-CoV-2 virions (2×10 4 PFU/mL diluted in growth media) were exposed to 5, 10, 15, and 20% (w/v) of an aqueous suspension of sintered Si3N4 particles for durations of 1, 5, and 10 minutes, respectively.…”
Section: Antibacterial and Antiviral Particles And Coatingsmentioning
confidence: 99%
“…It has proven to be effective against a range of gram-positive and -negative bacteria [23][24][25][26][27][28][29][30][31][32][33][34] along with some fungi [35,36], and its effectivity appears to be at least equivalent to other antimicrobial agents. Recent publications demonstrated its ability to rapidly inactivate viruses including SARS-CoV-2 [37][38][39][40]. In this study, it was hypothesized that non-woven fabric embedded with Si 3 N 4 would not only trap viral droplets and particles, but also render them harmless.…”
Section: Introductionmentioning
confidence: 97%